THE EFFECT OF SOCIAL MEDIA INFLUENCER (RADITYA DIKA) ON PURCHASE INTENTION (BIBIT) THROUGH CORPORATE REPUTATION BRAND ATTITUDE AND PERCEIVED VALUE - Todoan Faldy; Lenny Christina Nawangsari (Jurnal Scientia, 2023)
This study aims to analyze the influence of social media influencers on purchase intention through corporate reputation, brand attitude and perceived value. This research was conducted on Seed users who are the millennial generation. The sampling technique used is stratified random sampling and data analysis using Smart PLS 3. The results of the analysis show that social media influencers have an influence on corporate reputation, brand attitude and perceived value. The results of the study also show that corporate reputation, brand attitude and perceived value have an influence on purchase intention. The results also show that social media influencers have an influence on purchase intention through corporate reputation and perceived value.